1999
DOI: 10.1034/j.1399-3054.1999.106203.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of an aspartic protease from potato tuber that is inhibited by a basic chitinase

Abstract: A protease was isolated from potato (Solanum tuberosum L. cv. Huinkul) tuber disks after 24 h of aeration when proteolysis is markedly increased. Purification was performed by ammonium sulfate precipitation, ion exchange chromatography, and affinity chromatography. A size of 40 kDa was estimated by sodium dodecyl sulphate‐polyacrylamide gel electrophoresis (SDS‐PAGE) and gel filtration, it is monomeric and its properties are consistent with those of aspartic proteinases (EC 3.4.23): it had a pH optimum between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 35 publications
(46 reference statements)
5
61
1
3
Order By: Relevance
“…However, it has significant similarity to two pathogenesis-related proteins, tobacco PRP-la and tomato PR leaf protein p14. Our results (Guevara et al, 1999) and those reported by Yamakawa et al (1998) suggest a new, still unknown physiological role for P25TI and its related proteins in plants.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, it has significant similarity to two pathogenesis-related proteins, tobacco PRP-la and tomato PR leaf protein p14. Our results (Guevara et al, 1999) and those reported by Yamakawa et al (1998) suggest a new, still unknown physiological role for P25TI and its related proteins in plants.…”
Section: Introductionsupporting
confidence: 77%
“…However, in a previous work, we have described that a potato basic chitinase strongly inhibited the activity of an aspartic protease isolated from the same source (Guevara et al, 1999). These results indicate that at least one member of the family of plant proteins with chitinase activity may have an endogenous role in the regulation of proteases.…”
Section: Introductionmentioning
confidence: 55%
“…We have identified three potato (Solanum tuberosum) aspartic proteases, one from tubers (StAP1) (Guevara et al, 1999) and two from leaves (StAP2 and StAP3) (Guevara et al, 2001). Two of these isoforms, StAP1 and StAP3, have been purified and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Sterile disks (10 mm diameter, 2 mm thick) of potato tuber were prepared, washed extensively and suspended in sterile water (15 disks in 23 ml water) and aerated for 24 h at 25 uC in an orbital shaker at 60 cycles min 21 . StAP1 was purified from tubers using the protocol previously described by Guevara et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…The nitrocellulose sheet was soaked for 2 h with a solution containing 100 mM Tris-HCl, pH 8.0 and 1% (w/v) BSA. The membrane was washed four times with 100 mM TrisHCl, pH 8.0 containing 150 mM NaCl and 0.05% (v/v) Tween 20 (TBST) and then incubated overnight with rabbit anti-StAP1 (1:10,000 v/v; Guevara et al 1999) in 100 mM Tris-HCl, pH 8.0, and 1% BSA. After four washes with TBST solution, the blot was allowed to react for 2 h with goat anti-rabbit antibody (1:10,000 v/v) labelled with alkaline phosphatase (Sigma).…”
Section: Gel Electrophoresis and Immunoblot Analysismentioning
confidence: 99%